Marketing and Branding Strategy of Breadfruit Chips with Creative Packaging to Reach the Millennial Generation in Wabula 1 Village, Buton Regency - Al Zarliani, Wa Ode; Wardana; Puranamasari, Wa Ode Dian; Ajo, Antasalam; Edy, Safrin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase the competitiveness of breadfruit chips products in Wabula 1 Village, Buton Regency, through branding strategies and creative packaging aimed at reaching the millennial generation market. The method used consists of three main stages: first, training and workshops to provide an understanding of the importance of branding, attractive packaging design, and the use of digital marketing; second, assistance in implementing the branding and packaging design strategies that have been learned, as well as the use of social media for promotion; third, product evaluation and promotion through market trials and various marketing channels, such as social media, local bazaars, and online marketplaces. The results of this activity showed that the training participants were very enthusiastic and gained new insights that were relevant to current market needs. Business actors are now better prepared to face market challenges, take advantage of digital opportunities, and introduce breadfruit chips products as quality local products. With this assistance and training, it is hoped that the breadfruit chips business can grow more rapidly and be known more widely, both in the local market and the larger market.